A study on development of ear ossicles from prenatal to postnatal life of humans - M., Sushma; K., Lakshmi Kumari; D., Asha Latha (International Journal of Research in Medical Sciences, 2016)
Background: Malleus, incus and stapes are the three ear ossicles present in middle ear. The auditory ossicles of the middle ear have a fundamental role in transmission of sound. The aim of this study was to determine development of ear ossicles from prenatal to postnatal life which will be of great help for an ENT surgeon who should be well conversant with the anatomical details of middle ear prior to undertake reconstruction procedures for the improvement of sound conduction in conductive deafness. Methods: The study was conducted in 25 foetuses and 25 adult ossicles after removal from temporal bones of embalmed cadavers. Vernier caliperse was used to measure different morphometric parameters to study growth and development of ossicles. Results: Malleus: The average length of Malleus varies from 4 to 7.24mm in foetuses and adults respectively. The length of the anterior process was variable and some of the processes were quite long. Incus: The incus had minimum morphological variations in the ossicles. Its length ranges from 4.97-6.94mm. Stapes: The stapes had maximum morphological variations in the ossicles. The variations of stapes were in the neck, the cruses and the foot plate. The variations seen in stapes were no neck, a short or a long neck. The cruses of the stapes had symmetry or asymmetry. Length varies from 2.45-3.8mm. Conclusions: Ossicles at 20 weeks of prenatal life were cartilagenous, and at 24 weeks they were ossified and surrounded by mesenchyme. Postnatal changes were minimal. These parameters of Ossicles will help in designing of implants and treating hearing loss.